Intra-Ethnic Racial Differences in Waterpipe Tobacco Smoking among Latinos?. (2nd January 2019) - Ortiz, Kasim; Cuevas, Adolfo G.; Salloum, Ramzi; Lopez, Nancy; LaVeist-Ramos, Thomas
ABSTRACT: Background and Objectives : This study examined differences in waterpipe smoking (both lifetime and current) by race and ethnicity. More specifically, we evaluated intra-ethnic racial differences among Latinos using a nationally representative sample. Methods : Pooled data from the National Adult Tobacco Survey (NATS) [2012-2014] was used, in which Log-Poisson multivariable regression models were deployed to determine the prevalence of waterpipe smoking behavior. Models were stratified by gender and we further investigated acculturation, controlling for relevant sociodemographic characteristics. Results : In fully-adjusted models assessing lifetime WTS, Black Latinos and White Latinos exhibited an increase prevalence of lifetime WTS compared to their non-Hispanic white counterparts. Once stratifying by gender, Black Latino men (PR = 1.49; 95% CI = 1.16, 1.90) exhibited increased prevalence of lifetime WTS compared to their non-Hispanic white men counterparts; although white Latino men (PR = 0.88; 95% CI = 0.80, 0.98) exhibited decreased prevalence compared to their non-Hispanic white male counterparts. Similar trends were found for current WTS among men. In fully adjusted models assessing lifetime WTS, among women, only white Latina's (PR = 1.23; 95% CI = 1.04, 1.46) exhibited increased prevalence compared to their non-Hispanic white women counterparts. When evaluating current WTS, Black Latina's (PR = 2.19; 95% CI = 1.32, 3.65) and white Latinas (PR = 1.28; 95% CI = 1.00, 1.63) exhibited increased prevalence of WTS compared to their non-Hispanic white women counterparts. Conclusions/Importance : Among the U.S. general adult population, intra-ethnic racial differences in WTS behaviors exist among Latinos; and is shaped by gender. Future efforts to eliminate racial disparities in WTS should be attentive intra-ethnic racial differences among Latinos.